THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE¬¬¬¬¬¬¬¬¬¬, LIQUIDITY AND PROFITABILITY ON TAX AGGRESSIVENESS ON TAX AGGRESSIVENESS (EMPIRICAL STUDY OF MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2015 -2017) - DZIKRI, ZUHRATULLAILI (Jurnal Ilmiah Mahasiswa FEB, 2018)
There are many tax aggressiveness in the world including Indonesia, in 2012 there are 4000 companies that report loss in its annual tax return for seven years and many of them is manufacturing companies. This research aims to examine the effect of corporate social responsibility disclosure, liquidity and profitability on tax aggressiveness in manufacturing companies that listed in Indonesia Stock Exchanges period 2015 to 2017. The data used in this research are secondary data from the official website of company. Population used are manufacturing companies that listed in Indonesia Stock Exchanges period 2015-2017. The samples of this research used 28 companies from 3 years were selected by purposive sampling method. The results showed that corporate social responsibility disclosure, liquidity and profitability have effect on tax aggressiveness. CSRD has significant positive effect on effective tax rate, the proxy of tax aggressiveness. Liquidity and profitability has significant negative effect on effective tax rate.Keywords: Tax aggressiveness, CSRD, liquidity, profitability